Patient Safety Culture and Associated Factors Among Health Care Providers in Bale Zone Hospitals, Southeast Ethiopia: An Institutional Based Cross-Sectional Study - Kumbi, Musa (Drug Healthc Patient Saf, 2020)
INTRODUCTION: Patient safety is a serious global public health issue and a critical component of health care quality. Unsafe patient care is associated with significant morbidity and mortality throughout the world. In Ethiopia health system delivery, there is little practical evidence of patient safety culture and associated factors. Therefore, this study aims to assess patient safety culture and associated factors among health care providers in Bale Zone hospitals. METHODS: A facility-based cross-sectional study was undertaken using the “Hospital Survey on Patient Safety Culture (HSOPSC)” questionnaire. A total of 518 health care providers were interviewed. Analysis of variance (ANOVA) was employed to examine statistical differences between hospitals and patient safety culture dimensions. We also computed internal consistency coefficients and exploratory factor analysis. Bivariate and multivariate linear regression analyses were performed using SPSS version 20. The level of significance was established using 95% confidence intervals and a p-value of <0.05. RESULTS: The overall level of patient safety culture was 44% (95% CI: 43.3–44.6) with a response rate of 93.2%. Factor analysis indicated that hours worked per week, participation in a patient safety program, reporting of adverse events, communication openness, teamwork within hospital, organizational learning and exchange of feedback about error were among factors that were significantly associated with the patient safety culture. CONCLUSION: According to the Agency for Health Research and Quality, the overall classification of patient safety score and most of the scores related to dimensions were low. Hours worked per week, participation in a patient safety program, reporting of adverse events and most safety dimensions were found to be factors associated with patient safety culture. Well-designed patient safety interventions need to be integrated with organizational policies to address all dimensions of patient safety culture.